Analisis Rasio Pajak/Tax Ratio Penghasilan dan Pola Konsumsi Dosen dan Karyawan Tetap ITB Ahmad Dahlan - Erion Erion; Taryana Harun (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2021)
The tax ratio is the ratio between tax revenue collected by a country and Gross Domestic Product. In measuring the tax ratio, Indonesia only includes elements of central tax revenue. The high level of compliance with paying taxes depends on trust from citizens of the government and vice versa. This study aims to examine and analyze how the influence of the tax base factors and tax rates on the level of tax ratios, review and analyze tax engineering links to avoid higher taxes, and Seeing the effect of the Taxable Deductible on the amount of the tax ratio. This type of research is a survey with a descriptive analysis method in which lecturers and permanent ITB Ahmad Dahlan Jakarta employees are the populations. Our results concluded that the higher the income, the higher the income tax due to the application of the progressive tax rate. Furthermore, the higher the income tax paid, the higher the tax ratio.